Oral History Interview with Lily Kong - Kong, Lily (Institutional Knowledge at Singapore Management University, 2018)
The interview covered: President – Career in Singapore prior to joining SMU Teaching & Curriculum – Blue Ribbon Commission for Undergraduate Education Campus – Prinsep Street Residences Teaching & Curriculum – SMU-X courses Research – Societal Challenges Teaching & Curriculum -SMU Academy